A longitudinal study of multiple lifestyle health risk behaviours among nursing students and non-nursing peers - Kritsotakis, George; Georgiou, Evangelos D.; Karakonstandakis, Georgios; Kaparounakis, Nikos; Pitsouni, Vasiliki; Sarafis, Pavlos (My University, 2020)
Aim: The aim of this paper is to compare the evolution of health risk behaviours between undergraduate nursing and social work students. Background: Nursing includes the promotion of health and the shaping of healthy behaviours. An important determinant for providing lifestyle advice is the lifestyle of nurses themselves. Design: Longitudinal comparative study. Measurements: We compared lifestyle risk behaviours (binge drinking, cannabis/hashish/marijuana use, smoking, oral hygiene/toothbrushing, breakfast/fruit/vegetable consumption, physical activity and screen time/sedentary behaviours) using a self-administered standardized questionnaire in nursing (n = 121) and social work (n = 140) students at the beginning (2012) and the end of their studies (2015). Adjusted multivariable logistic/Poisson regression models were performed. Results: There were no statistically significant differences between the departments in most risk factors in both assessments. However, in relation to their first year, both nursing and social work students displayed higher relative risk of engaging in more behavioural risk factors at the end of their studies (in delivery/junk food consumption, sunburns, hashish/marijuana use and multiple sexual partners). Social work students displayed better behaviours in physical activity and breakfast intake. Conclusion: Nursing students share the patterns of their nonnursing peers in behavioural risk factors compromising their future health and health-promoting role. We need strategies to safeguard the professional nursing practice.
Keywords: Health promotion; Health risk behaviours; Lifestyle; Nurses; Students; Undergraduate education